Uji Kemampuan Umbi Gadung (Dioscorea Hispida) Dan Buah Bintaro (Cerbera Manghas) Dalam Mematikan Tikus - Hamsir Ahmad; Abd Rahman (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
The existence of rats is very disturbing and endangers human life because of the role of rats as agents that spread Murine thypus, Leptospirosis, and Salmonellosis. Natural rodenticides that can be used to kill rats with the use of vegetable rodenticides ie. gadung tubers and bintaro fruit because they contain toxic chemicals This research is a pseudo-experiment (Quasi Experimental) with the aim of determining the ability of gadung tubers (Dioscorea hispida) and bintaro fruit (Cerbera magas) in killing rat pests with doses of 20 grams, 40 grams and 60 grams and control with observation time for 10 days, replication was carried out 2 times. The results showed that a dose of 20 grams of gadung tubers can kill rats by 50%, a dose of 40 grams can kill rats by 66%, a dose of 60 grams can kill rats by 66% while a dose of bintaro shows a dose of 20 grams can kill rats by 66%, a dose of 40 grams can kill rats by 33%, a dose of 60 grams can kill rats by 16%. The conclusion of this study is that the results of the study proved that gadung tubers (Dioscorea hispida) with doses of 20 gr, 40 gr and 60 gr were able to kill rats because they had met the requirements for 50% rat death and 20 gr of bintaro fruit (Cerbera magas) was able to kill rats because it had met the requirements for 50% rat death. While at doses of 40 gr and 60 gr are not able to kill rats because they do not meet the requirements of 50% mortality in rats. People can use vegetable rodenticides of gadung tubers 40 grams and bintaro fruit 20 grams as an alternative for environmentally friendly rat control because the treatment is able to kill rats with a smaller dose and high mortality rate.